Dynamique de la mangrove de l’estuaire du Saloum (Sénégal) entre 1972 et 2010 - EL Hadji Balla Dieye; Amadou Tahirou Diaw; Tidiane Sané; Ngor Ndour (Cybergeo, 2013)
This study is carried out on the state of the Saloum estuary’s mangrove ecosystems, from 1972 to 2010, a period characterized by a climatic variability (drought) in West Africa. It is based on diachronic analysis of Landsat and SPOT satellite images (from 1972 to 1986, from 1986 to 2001 and from 2001 to 2010). Results show a negative overall evolution of the Saloum estuary’s mangrove at the rate of 34.8% characterized by a significant disappearance of the mangrove (38.3%) concentrated in the north-western periphery of the estuary and a very weak extension (3.5%) from 1972 to 1986. Between 1986 and 2001, one notices a relative stability (89.4%) but marked by a regeneration of the mangrove (14.38%) compared to a weaker regression (10.64%). From 2001, mangrove evolution remains weak (18.96%) but characterized by a drop of the disappearance (4.36%) with an increase of the regeneration (23.31%). The rainfall was found to be the main factor of the mangrove dynamics in the Saloum estuary. Efforts done by setting up the mangrove protection and development projects also allowed to increase the awareness of local populations to the necessity to take into account the mangrove degradation level and the urgency to safeguard this ecosystem.